Overestimated Balance Sheet — the Astray of Research Without Archival Sources. In Response to Kazimierz Przeszowski - Kuberski, Hubert (Faces of War, 2025)
The polemic reviews the research of Kazimierz Przeszowski, which was intended as a balance sheet of previous estimates by Stanisław Płoski and Ewa Śliwińska, Adam Borkiewicz, Hanns von Krannhals, Maria Turlejska, Antoni Przygoński, Joanna Hanson, Maja Motyl and Stanisław Rutkowski, Piotr Gursztyn, Norbert Bączyk and Grzegorz Jasiński, as well as Hubert Kuberski. These estimates indicate that the number of victims of the Wola massacre ranged from 10,000 to 57,600 (even 65,000). This part can be considered a precise summary of previous studies. However, the subsequent section of the article is based on statistical research derived from postwar historians’ studies (lacking statistical data from 1938–1944), which does not allow for detailed research. The comparative analysis of mass executions in Rumbula near Riga, Babi Yar near Kyiv, and executions carried out during Operation ‘Ertnefest’ [sic! actually — Aktion ‘Erntefest’] in Distrikt Lublin is even more problematic, as the author proves that German forces in Wola were sufficient to exterminate even 65,000 people. Przeszowski demonstrated that the Wola district was estimated to have been inhabited by around 100,000 people in the summer of 1944, potential victims of mass executions. These finding, indicate the need for a new methodological approach and further archival research into the number of human losses in Wola in 1944, particularly concerning the analysis of documents preserved in the Bundesarchiv. This place provides an orientation to the number of German, Austrian and Eastern European exterminators during the two-day danse macabre in Northern County — commonly known as the Wola district.